Application of xylanases from Amazon Forest fungal species in bleaching of eucalyptus kraft pulps - Medeiros,Roseli Garcia (2007)
Crude xylanase preparations from Penicillium corylophilum, Aspergillus niger and Trichoderma longibrachiatum were used to treat Eucalyptus kraft pulp, prior to chlorine dioxide and alkaline bleaching sequences. The enzyme pretreatment improved brightness and delignification of non-delignified and oxygen-bleached samples of eucalyptus kraft pulp. Xylanase preparations from T. longibrachiatum and P. corylophilum were more effective to reduce pulp kappa number. A small reduction in viscosity was obtained when the oxygen-bleached pulp was treated with xylanase preparation from A. niger. For all enzyme samples, the best release of chromophoric material from the pulp was at 237 nm. The enzyme preparation from P. corylophilum was responsible for the highest release of reducing sugar at a dosage interval of 10-20 IU/g dry weight pulp. Scanning electron microscopy studies of oxygen-bleached pulp after xylanase treatment revealed morphological changes, including holes, cracks, filament forming and peeling.